Solving Fractional Partial Differential Equations with Corrected Fourier Series Method - Nor Hafizah Zainal; Adem Kılıçman (Abstract and Applied Analysis)
The corrected Fourier series (CFS) is proposed for solving partial differential equations (PDEs) with fractional time derivative on a finite domain. In the previous work, we have been solving partial differential equations by using corrected Fourier series. The fractional derivatives are described in Riemann sense. Some numerical examples are presented to show the solutions.